Upaya Peningkatan Kesehatan Jiwa Anak Usia Toodler Melalui Terapi Kelompok Terapeutik di Puskesmas Gandus Palembang - Yani, Sri Endri; Susanti, Eva; Haryanti, Rizki Sri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Efforts to improve optimal mental health for each individual, family and community can be done with various approaches. The participation and support of the family and the environment in achieving mental health conditions can be done by accompanying the growth and development of children at every stage of their development. The development of toddler age children needs to be maximized by stimulating personality, psychomotor, cognitive and social development through therapeutic group therapy. The implementation of toddler therapeutic group therapy at the Gandus Health Center in Palembang was attended by ten mothers and ten toddler age children. The implementation of therapeutic group therapy improves the family's ability to provide stimulation for the development of toddler age children will be able to help overcome problems in family members, especially in terms of development, sharing experiences in providing stimulation for child development to help children develop the stages of autonomy and independence of toddler age children which is the basis for self-confidence in children. child.